Detrimental effects of sleep deprivation on the regulatory mechanisms of postural balance: a comprehensive review - Paillard, Thierry (Frontiers in Human Neuroscience, 2023)
This review addresses the effects of sleep deprivation on postural balance based on a comprehensive search of articles dealing with this relationship in the electronic databases PubMed, Google Scholar and ScienceDirect. Evidence suggests that postural balance is sensitive to acute and chronic sleep deprivation for everyone, including young and healthy subjects. Pathologies, aging and the circadian pattern aggravate and/or accentuate the effects of sleep deprivation on postural balance. It turns out that the different systems of information taking, decision making and motor execution of the postural balance function are negatively affected by sleep deprivation. For example, regarding the information taking system, the sensitivity of visual perception and visuo-spatial performance and the oculomotricity are disrupted and the vestibulo-ocular reflex and the sensory reweighting are altered. Regarding the decision making system, the different brain areas activated for the regulation of postural balance are less active after sleep deprivation and the executive function and perception of verticality are impaired. Regarding the motor execution system, the agonist-antagonist muscle coordination can be modified. However, the different detrimental effects induced for each system of the postural balance function are not yet fully known and deserve further exploration in order to better understand them.